A reversible transformation of functional groups in graphene oxide with loading and unloading of metal compounds. (April 2016) - Zhang, Xiaoting; Zhou, Jisheng; Song, Huaihe; Liu, Chengcheng; Zhang, Su; Chen, Xiaohong
Abstract: Functional groups (FGs) in graphene oxide (GO) play an important role in the properties and applications of GO and its related materials. However, there are limited studies about the reversible transformation of FGs in response to external stimuli. In this paper, we report an experimental investigation on the response of FGs to the stimuli of transitional metal compounds. Reversible transformation of FGs on GO with loading and unloading of metal compounds was found. This interesting phenomenon could be helpful to not only enrich the reactivity of FGs in GO, but also provide new insights for designing advanced graphene-based nanomaterials.